Glacial isostatic uplift of the European Alps - Mey, Jürgen; Scherler, Dirk; Wickert, Andrew D.; Egholm, David L.; Schildgen, Taylor F.; Strecker, Manfred R.; TESAURO, MAGDALA (Nature Communications, 2016)
Following the last glacial maximum (LGM), the demise of continental ice sheets induced crustal rebound in tectonically stable regions of North America and Scandinavia that is still ongoing. Unlike the ice sheets, the Alpine ice cap developed in an orogen where the measured uplift is potentially attributed to tectonic shortening, lithospheric delamination and unloading due to deglaciation and erosion. Here we show that ∼90% of the geodetically measured rock uplift in the Alps can be explained by the Earth's viscoelastic response to LGM deglaciation. We modelled rock uplift by reconstructing the Alpine ice cap, while accounting for postglacial erosion, sediment deposition and spatial variations in lithospheric rigidity. Clusters of excessive uplift in the Rhône Valley and in the Eastern Alps delineate regions potentially affected by mantle processes, crustal heterogeneity and active tectonics. Our study shows that even small LGM ice caps can dominate present-day rock uplift in tectonically active regions.